Anti-merozoite antibodies induce natural killer cell effector function and are associated with immunity against malaria - Odera, Dennis; Tuju, James; Mwai, Kennedy; Nkumama, Irene Nailain; Fürle, Kristin; Chege, Timothy; Kimathi, Rinter; Diehl, Stefan; Musasia, Fauzia K.; Rosenkranz, Micha; Njuguna, Patricia; Hamaluba, Mainga; et al. (Science translational medicine, 2023)
Natural killer (NK) cells are potent immune effectors that can be activated via antibody-mediated Fc receptor engagement. Using multiparameter flow cytometry, we found that NK cells degranulate and release IFN-γ upon stimulation with antibody-opsonized Plasmodium falciparum merozoites. Antibody-dependent NK (Ab-NK) activity was largely strain transcending and enhanced invasion inhibition into erythrocytes. Ab-NK was associated with the successful control of parasitemia after experimental malaria challenge in African adults. In an independent cohort study in children, Ab-NK increased with age, was boosted by concurrent P. falciparum infections, and was associated with a lower risk of clinical episodes of malaria. Nine of the 14 vaccine candidates tested induced Ab-NK, including some less well-characterized antigens: P41, P113, MSP11, RHOPH3, and Pf_11363200. These data highlight an important role of Ab-NK activity in immunity against malaria and provide a potential mechanism for evaluating vaccine candidates.
Gesehen am 29.03.2023